Analysis of orthosis with biomechanical interventions and gait modifications for medial knee osteoarthritis patients / Saad Jawaid Khan - Saad Jawaid , Khan (2018)
The study aimed at (1) investigating the effects of altering foot progression angles on physical balance in healthy and medial knee osteoarthritis (kOA) participants, (2) assessing the immediate effects of orthoses (valgus knee brace and wedged insoles) and gait modification techniques (toe-in and toe-out gait) in improving the physical function of kOA participants, and (3) testing the hypothesis that toe-in gait will reduce first peak of knee adduction moment (fKAM), while toe-out gait will reduce its second peak (sKAM) when combined with knee brace and laterally wedged insoles in kOA patients. Biodex Balance System was used to measure postural stability and fall risk at different foot progression angles (from -20º to 40º, with 10º increments) on 20 healthy and 20 kOA patients randomly with different static and dynamic platform settings. Five performance-based tests: (1) 30-second Chair Stand Test (30CST) (2) 40m Fast-Paced Walk test (40FPW) (3) Stair Climb Test (SCT) (4) Timed Up-and-Go test (TUG) (5) 6-Minute Walk Test (6MWT) were applied on 20 healthy and 20 kOA patients randomly to measure physical function. fKAM and sKAM were determined through 3-dimensional gait analysis with nine randomized conditions: (1) N (natural gait, without any intervention), (2) brace, (3) brace + toe-in gait, (4) wedged insole, (5) wedged insole + toe-in gait, (6) knee brace + wedged insole + toe-in gait, (7) brace + toe-out gait, (8) wedged insole + toe-out gait, (9) brace + wedged insole + toe-out gait. Fall risk was assessed by the Biodex Balance System® using three stability settings, (i) static (ii) moderate dynamic setting (FR12) and (iii) high dynamic setting (FR8). Data from the tests were analyzed using independent sample t-test, 3-way mixed methods ANOVA and repeated-measures ANOVA. Platform settings had a significant interaction effect with participant group (p < 0.01) and toe angles (p < 0.01). Toe-out gait impaired the physical function while knee brace improved it during 40FPW, SCT and 6MWT. fKAM reduced maximally (19.7%) by brace + toe-in gait, while sKAM reduced maximally by brace + wedged insole + toe-out gait (25.5%). Fall risk increased significantly at FR8 when knee brace and wedged insoles were combined with toe-in gait (35.7%) and toe-out gait (42.9%). Changing platform settings had a more pronounced effect on balance in kOA group than healthy group. Changing toe angles produced similar effects in both the participant groups, with decreased stability and increased fall risk at extreme toe-in and toe-out angles. Physical function was improved maximally by the knee brace, while toe-out gait impaired it the most. There is a synergistic effect of toe-in gait and toe-out gait when combined with knee brace and wedged insole concurrently in the reductions in the first and the second peaks of knee adduction moment respectively but with a greater risk of fall.